Pattern Recognition of mtDNA with Associative Models - Acevedo, María Elena; Acevedo, Marco Antonio; Felipe, Federico; Aquino, David (MATEC web of conferences, 2016)
In this paper we applied an associative memory for the pattern recognition of mtDNA that can be useful to identify bodies and human remains. In particular, we used both morphological hetroassociative memories: max and min. We process the problem of pattern recognition as a classification task. Our proposal showed a correct recall, we obtained the 100% of recalling of all the learned patterns. We simulated a corrupted sample of mtDNA by adding noise of two types: additive and subtractive. The memory showed a correct recall when we applied less or equal than 55% of both types of noise.